Hypoxia-Inducible Factor as an Angiogenic Master Switch - Hashimoto, Takuya; Shibasaki, Futoshi (Frontiers in Pediatrics, 2015)
Hypoxia-inducible factors (HIFs) regulate the transcription of genes that mediate the response to hypoxia. HIFs are constantly expressed and degraded under normoxia, but stabilized under hypoxia. HIFs have been widely studied in physiological and pathological conditions and have been shown to contribute to the pathogenesis of various vascular diseases. In clinical settings, the HIF pathway has been studied for its role in inhibiting carcinogenesis. HIFs might also play a protective role in the pathology of ischemic diseases. Clinical trials of therapeutic angiogenesis after the administration of a single growth factor have yielded unsatisfactory or controversial results, possibly because the coordinated activity of different HIF-induced factors is necessary to induce mature vessel formation. Thus, manipulation of HIF activity to simultaneously induce a spectrum of angiogenic factors offers a superior strategy for therapeutic angiogenesis. Because HIF-2α plays an essential role in vascular remodeling, manipulation of HIF-2α is a promising approach to the treatment of ischemic diseases caused by arterial obstruction, where insufficient development of collateral vessels impedes effective therapy. eIF3e/INT6 interacts specifically with HIF-2α and induces the proteasome inhibitor-sensitive degradation of HIF-2α, independent of hypoxia and VHL. Treatment with eIF3e/INT6 siRNA stabilizes HIF-2α activity even under normoxic conditions and induces the expression of several angiogenic factors, at levels sufficient to produce functional arteries and veins in vivo. We have demonstrated that administration of eIF3e/INT6 siRNA to ischemic limbs or cold-injured brains reduces ischemic damage in animal models. This review summarizes the current understanding of the relationship between HIFs and vascular diseases. We also discuss novel oxygen-independent regulatory proteins that bind HIF-α and the implications of a new method for therapeutic angiogenesis using HIF stabilizers.